Recent trends in botanical pesticides - MAJUMDER, SUJAN; Paul, Anindita; Singh, Satyapriya; Divekar, Pratap A (Indian Farming, 2022)
The ever-increasing environmental burden created by chemical synthetic pesticides gave new life to botanical pesticides in a wider dimension, an evergreen and eco-friendly option for pest management. Several beneficial characteristics like ease of application, unique and versatile mode of action encourage their use. Though botanicals have yet to reach their full market potential due to the lack of formal regulatory approval, they are cheap and easy to produce. Hence, to cope up with the environmental stress and market surge, proper economical extraction of potential botanical active ingredients is the need of hour as an alternate strategy.